HUBUNGAN PEMBERIAN IMUNISASI DASAR DENGAN TUMBUH KEMBANG BAYI DI PUSKESMAS KECAMATAN SAWAH BESAR TAHUN 2021 - Hirfa, Turrahmi (Jurnal Ilmiah Bidan (JIB), 2023)
According to the World Health Organization (WHO), the infant mortality rate (IMR) has decreased in recent years. In 2017, the infant mortality rate was 29 deaths per 1000 live births. According to the Central Statistics Agency (BPS), the Infant Mortality Rate (IMR) in DKI Jakarta in 2012 was 22 per 1000 live births, and in 2015 the infant mortality rate was 18 per 1000 live births.2 Basic immunization is very important. given to infants aged 0-12 months to provide immunity from diseases that can be prevented by immunization (PD3I), including Tuberculosis, Diphtheria, Pertussis, Tetanus, Polio, Hepatitis B and Measles. The occurrence of growth and development can be caused because development is closely related to the maturation of individual organ functions. Therefore, this study examines whether there is a relationship between immunization and infant growth and development. This type of research uses a quantitative descriptive method with a cross sectional approach. The population in this study was the total number of infants who were given basic immunization at the Sawah Besar District Health Center. The sampling technique is by random sampling. The results showed that the percentage of basic immunization for infants was 85.7%, incomplete immunization was 14.3%. The percentage of good growth and development is 91.6%, growth is not good 8.6%. The conclusion that there is a relationship with the provision of basic immunization with infant growth and development P(0.000).